Protecting groundwater from leachate contamination: design of drainage system at Sa Kaeo Landfill, Thailand (Journal of Nepal Geological Society, 2006)
This study focuses on the design of a drainage layer at the Sa Kaeo LandfiII, Thailand, to effectively isolate its leachate. The leachate thickness build-up in the granular layer of the primary leachate collection and removal system (PLCRS) as well as the geocomposite layer of the secondary leachate collection and removal system (SLCRS) was calculated from the measured values of apparent permeability of gravels and transmissivity of geocomposite, and compression and creep factors of geonet at site-specific boundary conditions. To evaluate the efficiency of granular and geosynthetic drainage materials in terms of leachate isolation, hydraulic safety factors were calculated for four landfill lives (i.e. for 1, 2, 10, and 100 years). The results show that the hydraulic safety factor decreases with a decrease in slope angle, increase in landfill life, and increase in drainage length. The safety factor of the PLCRS for landfill life of 100 years under Module 1 (with a drainage length of 138 m) is 29.0 and 2.2 in coarse and fine gravels (commercial size of 1.905 and 0.318 cm) respectively. This safety factor corresponds to the slope gradient of 0.01 at the worst case of leachate production (when all rainfall enters into the drainage system as leachate). Under Module 2 (with a drainage length of 183 m) the safety factor reduced by 22- 25% in comparison with that of Module 1. Similarly, the safety factor of the SLCRS drastically decreases from 50.4 to 0.8 at a leachate leakage rate of 10% of the maximum rainfall when the land fill life is increased from 1 to 100 years. However, the leachate thickness in the PLRS and SLCRS is less than their saturated thickness in both modules. Hence it is concluded that Module 1 is relatively more efficient than Module 2 at lower slope gradients (i.e. 0.01).